2017
DOI: 10.1021/acs.biochem.6b01152
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Interactions as Mediators in the Allosteric Activation of Protein Kinase A RIα

Abstract: Close-range electrostatic interactions that form salt bridges are key components of protein stability. Here we investigate the role of these charged interactions in modulating the allosteric activation of protein kinase A (PKA) via computational and experimental mutational studies of a conserved basic patch located in the regulatory subunit's B/C helix. Molecular dynamics simulations evidenced the presence of an extended network of fluctuating salt bridges spanning the helix and connecting the two cAMP binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…Finally, disruption of the salt bridge, especially one that involved two negative charges, may induce protein remodeling through partial unfolding due to the colocalization of two negatively charged side chains. Similar reorganizations of electrostatic networks and allosteric effects resulting from disrupted charge clusters have also been observed in other systems, including PKA and VraR (40,41). These examples as well as others (42) suggest that neither mono-nor divalent cation binding would completely recover the energy invested in the colocalization of D134 and E135 in RKIP, and, thermodynamically, the partial unfolding of the loop is favored.…”
supporting
confidence: 66%
“…Finally, disruption of the salt bridge, especially one that involved two negative charges, may induce protein remodeling through partial unfolding due to the colocalization of two negatively charged side chains. Similar reorganizations of electrostatic networks and allosteric effects resulting from disrupted charge clusters have also been observed in other systems, including PKA and VraR (40,41). These examples as well as others (42) suggest that neither mono-nor divalent cation binding would completely recover the energy invested in the colocalization of D134 and E135 in RKIP, and, thermodynamically, the partial unfolding of the loop is favored.…”
supporting
confidence: 66%
“…The thermodynamic properties of the 2 CNB domains are critically intertwined and sensitive to ligand binding as well as mutation of the neighbor (41). Both mutagenesis and simulations have shown that the helical propensity of the αB/C/N-helix correlates with R-C dissociation in the (Δ1-91) RIα:C complex (42). The "flip-back" model of the R-C complex, which has been observed in long MD simulations, also highlights the dynamic properties of the αB/C/N-helix and the CNB domains for PKA activation (43).…”
Section: Resultsmentioning
confidence: 99%
“…Such mobility of the CNB-B domain is consistent with previously obtained SAXS data of the RIα(91-379):PKAcα heterodimer and led to a suggestion that the CNB-B domain of RIα is mobile and moves away from PKAcα with Gly235 serving as a hinge point (Cheng et al, 2009). Recent studies have shown that CNB-B domain flexibility is linked to cAMP activation in the RIα(91-379):PKAcα truncated heterodimer (Hirakis et al, 2017; Barros et al, 2017). However, this view of CNB-B movement in the holoenzyme is different from the packing observed here in the full-length chimeric and wt RIα holoenzymes (Figures.…”
Section: Resultsmentioning
confidence: 99%